Specific pathogens and microbial abundance within liver and kidney tissues of wild marine fish from the Eastern Mediterranean Sea. Issue 3 (14th February 2020) - Meron, Dalit; Davidovich, Nadav; Ofek‐Lalzar, Maya; Berzak, Ran; Scheinin, Aviad; Regev, Yael; Diga, Rei; Tchernov, Dan; Morick, Danny
Summary: This study is an initial description and discussion of the kidney and liver microbial communities of five common fish species sampled from four sites along the Eastern Mediterranean Sea shoreline. The goals of the present study were to establish a baseline dataset of microbial communities associated with the tissues of wild marine fish, in order to examine species‐specific microbial characteristics and to screen for candidate pathogens. This issue is especially relevant due to the development of mariculture farms and the possible transmission of pathogens from wild to farmed fish and vice versa. Although fish were apparently healthy, 16S rRNA NGS screening identified three potential fish bacterial pathogens: Photobacterium damselae, Vibrio harveyi and Streptococcus iniae . Based on the distribution patterns and relative abundance, 16 samples were classified as potential pathogenic bacteria‐infected samples (PPBIS). Hence, PPBIS prevalence was significantly higher in kidneys than in liver samples and variation was found between the fish species. Significant differences were observed between fish species, organs and sites, indicating the importance of the environmental conditions on the fish microbiome. We applied a consistent sampling and analytical method for monitoring in long‐term surveys which may be incorporated within other marine fish pathogens surveys around the world. Abstract : This study is an initial description and discussion of the kidney and liver microbial communities of five common fish species sampled from four sites along the Eastern Mediterranean Sea shoreline. The goals of the present study were to establish a baseline dataset of microbial communities associated with the tissues of wild marine fish, in order to examine species‐specific microbial characteristics and to screen for candidate pathogens.